Persepsi Siswi SMA Negeri 2 Lubuk Basung tentang Pemilihan Sunscreeenberdasarkan Trend di Platform TikTok - Zahra Nopita; Mimi Yupelmi (CV. Doki Course and Training, 2026)
TikTok has emeged as one of the mostwidely accessed platforms for obtaining information about sunscreen product among adolescents. Despite its popularity, the extensive use of this platform does not necessarily ensure that users are able to choose sunscreen products that match their individual skin characteristics and needs. Therefore, this study conducted to examine the perceptions of female studenst at SMA Negeri 2 Lubuk Basung toward sunscreen selesction influenced by TikTok trends, focusing on cognitive, affective, and conative dimensions. A descriptive quantitative research design was employe, involving 164 female students who were selescted through proportional random sampling. Data were grathered using a questionnaire administered via Google Forms and Analyzed descriptively by calculating the Respondent Achievement Level (RAL) ccores. The findings indicate that the cognitive dimension was categorized as good (81.94%), the affective dimension as good (79,89%), and the conative dimension as good (82,62%). These findings suggest that although the students generally demonstrated positive perceptions regarding the selection of sunscreen products based on TikTok trends, they should be more critical in choosing products that suit their individual skin conditions to minimize the risk of using inappropriate sunscreen products.